Review on preservation techniques of edible lily bulbs in China. Issue 1 (31st December 2022) - Yang, Wenzhe; Wang, Peng; Zhang, Wen; Xu, Mengda; Yan, Lihong; Yan, Ziyi; Du, Wanhua; Ouyang, Lu; Liu, Bin; Wu, Zijian; Zhang, Zhe; Zhao, Songsong; et al.
ABSTRACT: Chinese sweet lily (Lilium davidii var. unicolor), the only edible lily in the world, has high nutritional value. At present, the application of preservation technology is relatively backward, resulting in a large loss of lily. Therefore, the preservation has become one of the key factors limiting the development of the edible lily bulbs industry. This paper reviews the various application of pretreatment and storage technologies for the preservation of lily bulbs. It is considered that irradiation and proper preservative can be used for pretreatment. Vacuum packaging can be used for short-term storage and transportation. Phase temperature storage could be as a long-term storage mode of lily bulbs.